Circulating IL-17A Levels in Postmenopausal Women with Primary Hyperparathyroidism - E. Dozio; E. Passeri; E. Vianello; S. Palmieri; C. Eller-Vainicher; M. Corsi Romanelli; S. Corbetta (Hindawi Limited, 2020)
Background. Primary hyperparathyroidism (PHPT) is a common cause of secondary osteoporosis in postmenopausal women. Th17 lymphocytes and the released cytokine IL-17A play an important role in bone metabolism. Th17 cells have been shown to be activated by PTH, and peripheral blood T cells from patients affected with PHPT express higher levels of IL-17A mRNA than controls. Aim. To investigate circulating levels of IL-17A and the ratio RANKL/OPG, as markers of osteoclastogenesis, in 50 postmenopausal PHPT women compared with postmenopausal osteoporotic non-PHPT women (n=20). Results. Circulating levels of IL-17A were similarly detectable in most PHPT and non-PHPT osteoporotic women (12.9 (8.4-23.1) vs. 11.3 (8.3-14.3) pg/ml, median (range interquartile), P=0.759), at variance with premenopausal women where IL-17A was undetectable. In PHPT women, any significant correlations could be detected between circulating IL-17A levels and PTH levels. Nonetheless, significant negative correlations between circulating IL-17A and ionized calcium levels (r=‐0.294, P=0.047) and urine calcium excretions (r=‐0.300, P=0.045) were found. Moreover, PHPT women were characterized by positive correlations between IL-17A levels and femur neck (r=0.364, P=0.021) and total hip (r=0.353, P=0.015) T-scores. Circulating IL-17A levels did not show any significant correlation with sRANKL, OPG, and sRANKL/OPG ratio in PHPT women. Conclusions. In postmenopausal PHPT women, circulating IL-17A levels were similar to those detected in postmenopausal non-PHPT women, showing a disruption of the relationship observed in postmenopausal osteoporosis among circulating PTH, sRANKL, OPG, IL-17A, and bone demineralization in postmenopausal PHPT women. The data support an osteogenic effect of IL-17A in postmenopausal PHPT women.